G GAVREED2 May 2010 64 0 Palmy May 24, 2010 #1 Can someone show me how to do this question. Thanks heaps y=x^2-3x-2 y=2x+4

harish21 Feb 2010 1,036 386 Dirty South May 24, 2010 #2 GAVREED2 said: Can someone show me how to do this question. Thanks heaps y=x^2-3x-2 y=2x+4 Click to expand... so you can write: \(\displaystyle y = y\) \(\displaystyle x^2-3x-2 = 2x+4\) \(\displaystyle x^2-3x-2 -2x-4=0\) \(\displaystyle x^2-5x-6 = 0\) can you solve this quadratic equation for x? Reactions: GAVREED2

GAVREED2 said: Can someone show me how to do this question. Thanks heaps y=x^2-3x-2 y=2x+4 Click to expand... so you can write: \(\displaystyle y = y\) \(\displaystyle x^2-3x-2 = 2x+4\) \(\displaystyle x^2-3x-2 -2x-4=0\) \(\displaystyle x^2-5x-6 = 0\) can you solve this quadratic equation for x?